Comparison of facilities with and without additional medical fees for nutrition support team activity during the COVID-19 pandemic - Akihiko Futamura; Takenao Koseki; Junichi Iida; Akito Suzuki; Nobuyuki Muroi; Michiaki Myotoku; Hiroki Maki; Kazuhisa Mizutani; Hikaru Ogino; Yasuki Taniguchi; Keiichiro Higashi; Masanobu Usui (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background This study aimed to clarify the effectiveness of nutrition support team (NST) facilities for preventing central line-associated bloodstream infection (CLABSI). Methods We retrospectively analyzed the incidence of CLABSI as well as the presence or absence of additional medical fees for NST activity between 2019 and 2021, including the period before and after the COVID-19 pandemic. Subsequently, we performed between-group comparisons of the CLABSI incidence. CLABSI rates were compared based on cumulative per 1000 catheter uses during the relevant period. Results Among 47 facilities that were registered for participation, there were 34 and 13 facilities with and without additional medical fees for NST activity (NST and non-NST groups, respectively). The CLABSI incidence rate was significantly lower in the NST group 0.96 [0.28–1.73] than in the non-NST group 1.25 [075–6.10] (p < 0.05). Before the pandemic, the NST group had a lower CLABSI rate per 1000 catheter uses than the non-NST group 2019: 0.70 [0.12–1.26] vs 2.10 [0.62–5.97]. During the pandemic, the CLABSI incidence showed no significant between-group difference 2020: 0.99 [0.51–1.61] vs 1.01 [0.80–4.16]; 2021: 1.24 [0.44–2.35] vs 1.96 [1.23–5.31]; however, the CLABSI rates in the NST group remained low. Conclusion During the COVID-19 pandemic, the incidence of CLABSI was lower in the NST group than in the non-NST group, indicating the effectiveness of NST in preventing the occurrence of CLABSI.